2010
DOI: 10.1002/mrm.22263
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between brain R2 and liver and serum Iron concentrations in elderly men

Abstract: Studies of iron overload in humans and animals suggest that brain iron concentrations may be related in a regionally specific way to body iron status. However, few quantitative studies have investigated the associations between peripheral and regional brain iron in a normal elderly cohort. To examine these relationships, we used MRI to measure the proton transverse relaxation rate (R 2 ) in 13 gray and white matter brain regions in 18 elderly men (average age, 75.5 years) with normal cognition. Brain R 2 value… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
34
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(35 citation statements)
references
References 32 publications
1
34
0
Order By: Relevance
“…Previous studies identified an association between iron accumulation in the basal ganglia of elderly men and peripheral iron measures [13]. However, only 9% of the variance of CSF ferritin can be explained by plasma ferritin [9], highlighting the separation between these compartments.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Previous studies identified an association between iron accumulation in the basal ganglia of elderly men and peripheral iron measures [13]. However, only 9% of the variance of CSF ferritin can be explained by plasma ferritin [9], highlighting the separation between these compartments.…”
Section: Discussionmentioning
confidence: 93%
“…Quantitative MRI studies measuring the proton transverse relaxation rate (R 2 ) now allow iron concentrations to be assessed in the brain in vivo. One such study in cognitively normal elderly men found that iron levels in basal ganglia structures were correlated with serum iron measures [13]. In an investigation in the large Australian Imaging Biomarker and Lifestyle (AIBL) cohort of healthy controls, MCI and AD patients had disturbed brain iron metabolism reflected in the periphery by a decrease in plasma iron and hemoglobin [14], which was due to a deficiency of iron-loading onto transferrin [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, serum ferritin or transferrin saturation levels do not correlate well with hepatic iron content in most cases of hyperferritinemia [39]. In a study of older communitydwelling males (mean age 75.5 years), serum ferritin levels did not correlate with regional brain iron contents as gauged by magnetic resonance imaging proton transverse relaxation rate (R 2 ) [40]. Furthermore, in neuroferritinopathy, caused by mutations in ferritin light chain, abnormal iron deposition occurs in regions such as the basal ganglia despite low or normal serum ferritin [13,14,41] and neither venesection nor iron chelation is beneficial [41].…”
Section: Discussionmentioning
confidence: 96%
“…Women begin their postmenopausal years in a state of relative peripheral iron deficiency compared with men and their iron levels increase for the first 15-20 years after menopause without fully 'catching up' to those in men (Whitfield et al, 2003). As the peripheral iron levels can influence brain iron accumulation (Bartzokis et al, 2007c;House et al, 2010;Li et al, 2010), these peripheral effects could manifest in the brain. Thus, as the two genders approach older ages, it is possible that the already higher levels of iron observed in men push them into a toxic range earlier as they enter older ages, whereas women, who start with considerably lower iron levels, may initially experience a cognitive benefit from increasing postmenopausal iron levels.…”
Section: Discussionmentioning
confidence: 99%